Problems with collaborative work and some possible solutions - Kabulov, Zoxidjon (Журнал иностранных языков и лингвистики, 2021)
This article deals with problems with collaborative work and its possible solutions. Works and opinions of some scholars and researchers are analyzed and summarized.